The Effect of Lavender Inhalation on the Pain Perception of Orthodontic Separator Placement: An Open-Label Randomized Controlled Trial - Maryam Tazarvi Fard Shirazi; Maryam Karandish (Tehran University of Medical Sciences, 2022)
Lavandula angustifolia Mill. (lavender) is known for its antibacterial, muscle relaxant, antispasmodic, sedative, and anesthetic effects, and is also proposed to be used as an analgesic agent. Despite several studies on the analgesic activity of lavender, this is the first experiment in patients with orthodontic pain. This "2-arm parallel" study aims to evaluate the effect of lavender oil inhalation on reducing pain after elastomeric separator placement as a part of orthodontic treatment. Patients who needed elastic separator placement in mesial and distal of first permanent molars of all quadrants prior to their first-ever fixed orthodontic treatment, with the age range of 20 to 24, were randomly assigned to one of the two study groups: lavender oil and sesame oil. Participants had to breathe in their medication for 2 minutes just before separator insertion, as well as 4, 8, 12, 24, 36, and 48 h afterward. A visual analog scale (VAS) was used to measure the level of pain during three oral situations, including rest, fitting posterior teeth, and chewing at the following periods: just before separator placement (T0), immediately after insertion (T1), 3 h post-insertion (T2), 12 h post-(T3), 24 insertion h post-insertion (T4), and 48 h after separator placement (T5). The current study indicated the effectiveness of lavender oil inhalation in reducing pain perception while chewing 48 h after elastic separator placement. The pain level in lavender inhalation was lower from 12 h to 48 h after separator insertion, although not considerable, indicating the probability of its effectiveness on delayed responses to orthodontic pain.